Crumbling Pillars: Understanding Institutional Decay in Indian Democracy - Ali, Hassan (Journal of Development and Social Sciences, 2024)
This study is designed to unveil problems in systemic functioning, constitutional lacunas and governance issues in Indian democracy. Due to these problems Indian democratic structure especially institutions are in decline. Key threats include crony capitalism, media manipulation, fascism, electoral malpractices, and human rights violations. International agencies have criticized the ruling regime's anti-democratic actions, with Freedom House declaring India "Partially Free" and V-Dem labeling it as "Electoral Autocracy.” To explore the causes of Institutional decay in India's democracy, the world's largest democracy. It uses comparative politics, democratic theory, and institutional theory to identify key threats. To highlight the problems and to propose viable solutions qualitative methodology is accompanied with interpretive method to grasp subjective issues. To address the underlying causes of institutional decline and increase democratic resilience, proposes institutional changes and policies and improve democratic governance. By understanding and resolving the root causes of institutional deterioration, the academic conversation on democratic governance by shedding light on the difficulties India's democratic institutions face and outlining potential paths for Improvement and revitalization.